Pemberdayaan Kewirausahaan Berbasis Ormas Keagamaan; Gerakan Wirausaha GP Ansor Desa Kendalrejo Pemalang - Mu’amar Ramadhan (LP2M of Institute for Research and Community Services - UIN Walisongo, 2019)
Entrepreneurship empowerment based on religious organizations at GP Ansor Kendalrejo Petarukan Pemalang was conducted in January-April 2019 with the methods: socialization, focus group discussion (FGD), and observation. These three mentoring methods are for the process of recruiting members, fostering interest and capacity building, as well as choosing the type and place of business. The next process is to assist in establishing the type of business undertaken by Ansor cadres in the form of the establishment of the